2016
DOI: 10.1113/jp272585
|View full text |Cite
|
Sign up to set email alerts
|

Studies using pharmacological blockade of muscle afferents provide new insights into the neurophysiology of perceived exertion

Abstract: International audience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The metabolic rate was shown to influence body size, resource use, rate of senescence and survival probability (Berghänel et al, 2015; Brown et al, 2004; DeLong et al, 2010; Munch and Salinas, 2009; Strotz et al, 2018; Voorhies and Ward, 1999). Preserving muscle effort may thus represent an essential pursuit for the brain (Baraduc et al, 2013; Bramble and Lieberman, 2004; Carrier et al, 2011; Cheval et al, 2018a, 2018b; Farshchiansadegh et al, 2016; Huang et al, 2012; Inzlicht et al, 2018; Kurzban et al, 2013; Lee et al, 2016; Lieberman, 2015; Mazzoni et al, 2007; Morel et al, 2017; Pageaux, 2016; Pageaux and Gaveau, 2016; Selinger et al, 2015; Shadmehr et al, 2016; Walton et al, 2006; Wang and Dounskaia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic rate was shown to influence body size, resource use, rate of senescence and survival probability (Berghänel et al, 2015; Brown et al, 2004; DeLong et al, 2010; Munch and Salinas, 2009; Strotz et al, 2018; Voorhies and Ward, 1999). Preserving muscle effort may thus represent an essential pursuit for the brain (Baraduc et al, 2013; Bramble and Lieberman, 2004; Carrier et al, 2011; Cheval et al, 2018a, 2018b; Farshchiansadegh et al, 2016; Huang et al, 2012; Inzlicht et al, 2018; Kurzban et al, 2013; Lee et al, 2016; Lieberman, 2015; Mazzoni et al, 2007; Morel et al, 2017; Pageaux, 2016; Pageaux and Gaveau, 2016; Selinger et al, 2015; Shadmehr et al, 2016; Walton et al, 2006; Wang and Dounskaia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…the combined model [70]). It should be noted that recent evidence provides support in favor of the corollary discharge model (for more details please see [71,65,72,73]). Yet without wishing to extend this discussion too much further, it can be stated that perception of effort could possibly be increased by 1) increasing the intensity of afferent feedback from peripheral physiological systems sensory signals, 2) increasing the intensity of central motor command (i.e.…”
Section: Psychologicalmentioning
confidence: 99%
“…This perception differs from other exercise-related sensations such as pain or discomfort (Pageaux, 2016), and can be rated via the use of psychophysiological scales such as the Borg ratings of perceived exertion scale or the category ratio (CR)10 scale (Borg, 1998). While a persistent debate exists in the literature on the neurophysiology of perceived exertion (Marcora, 2009; Pageaux, 2016), it exists strong experimental data providing evidence that perception of effort results from the neuronal process of the corollary discharge associated with the central motor command (Marcora, 2009; Pageaux, 2016; Pageaux and Gaveau, 2016). Indeed, studies using pharmacological blockade of muscle afferents demonstrated that in absence of muscle afferent feedback, perception of effort is not reduced during endurance exercise (Pageaux and Gaveau, 2016).…”
Section: Prior Physical Exertion and Prior Mental Exertion Increase Pmentioning
confidence: 99%
“…While a persistent debate exists in the literature on the neurophysiology of perceived exertion (Marcora, 2009; Pageaux, 2016), it exists strong experimental data providing evidence that perception of effort results from the neuronal process of the corollary discharge associated with the central motor command (Marcora, 2009; Pageaux, 2016; Pageaux and Gaveau, 2016). Indeed, studies using pharmacological blockade of muscle afferents demonstrated that in absence of muscle afferent feedback, perception of effort is not reduced during endurance exercise (Pageaux and Gaveau, 2016). While the increased perceived exertion in presence of fatigue of a muscle group involved in subsequent endurance exercise is associated with an increase in activity of cortical premotor and motor areas (i.e., index of central motor command) to compensate for alteration of neuromuscular properties of the working muscles (de Morree et al, 2012); the underlying mechanisms behind the increased perceived exertion induced by fatigue of a muscle group non-involved in subsequent endurance exercise and fatigue induced by mental exertion remain unclear.…”
Section: Prior Physical Exertion and Prior Mental Exertion Increase Pmentioning
confidence: 99%
See 1 more Smart Citation